About Making Lignin Great Again—Some Lessons From the Past - Glasser, Wolfgang G. (Frontiers in Chemistry, 2019)
Lignin, the second most abundant biopolymer on the planet, serves land-plants as bonding agent in juvenile cell tissues and as stiffening (modulus-building) agent in mature cell walls. The chemical structure analysis of cell wall lignins from two partially delignified wood species representing between 6 and 65% of total wood lignin has revealed that cell wall-bound lignins are virtually invariable in terms of inter-unit linkages, and resemble the native state. Variability is recognized as the result of isolation procedure. In native state, lignin has a low glass-to-rubber transition temperature and is part of a block copolymer with non-crystalline polysaccharides. This molecular architecture determines all of lignin's properties, foremost of all its failure to undergo interfacial failure by separation from (semi-) crystalline cellulose under a wide range of environmental conditions. This seemingly unexpected compatibility (on the nano-level) between a carbohydrate component and the highly aromatic lignin represents a lesson by nature that human technology is only now beginning to mimic. Since the isolation of lignin from lignocellulosic biomass (i.e., by pulping or biorefining) necessitates significant molecular alteration of lignin, isolated lignins are highly variable in structure and reflect the isolation method. While numerous procedures exist for converting isolated (carbon-rich) lignins into well-defined commodity chemicals by various liquefaction techniques (such as pyrolysis, hydrogenolysis, etc.), the use of lignin in man-made thermosetting and thermoplastic structural materials appears to offer greatest value. The well-recognized variabilities of isolated lignins can in large part be remedied by targeted chemical modification, and by adopting nature's principles of functionalization leading to inter-molecular compatibility. Lignins isolated from large-scale industrial delignification processes operating under invariable isolation conditions produce polymers of virtually invariable character. This makes lignin from pulp mills a potentially valuable biopolymeric resource. The restoration of molecular character resembling that in native plants is illustrated in this review via the demonstrated (and in part commercially-implemented) use of pulp lignins in bio-degradable (or compostable) polymeric materials.